Paleoproterozoic Greenstone-Granite Belts in Northern Brazil and the Former Guyana Shield - West African Craton Province - Ian McReath; Maria Telma Lins Faraco (Geologia USP. Série Científica, 2006)
The mainly meta-volcano-sedimentary Vila Nova Group and associated granites constitute separate belts, which formpart of a large paleoproterozoic (mainly rhyacian) province in the Guyana Shield of which northern Brazil forms a part, andthe West African Craton. In Brazil the southwestern Serra do Ipitinga and Serra Tumucumaque-Serra do Navio belts have noobvious geometrical extensions in the Guyanas or Venezuela, and may represent deposits formed at penecontemporaneouspassive continental margins and ocean floor spreading centres. To the Northeast the Serra Lombarda-Tartarugalzinho andOiapoque belts are continuations of Guianese belts. In the former the igneous rocks have geochemical characteristics ofsuprasubduction environments. Belts in the Guyana Shield and West African Craton have many similar features. Themegaprovince evolved in a number of stages, which may have started at about 2.3 Ga, and continued with diminished activityafter 2.11 Ga. Both major juvenile additions and (possibly minor) reworking of earlier crust contributed to the growth of theprovince. The major transcurrent deformation, responsible for the present structure of the belts, probably occurred duringthe later stages of evolution of the province, but metamorphism and deformation are registered even in the oldest rocks.